A swarm of autonomous miniature underwater robot drifters for exploring submesoscale ocean dynamics - Jules S. Jaffe (Nature Portfolio, 2017)
Observing dynamics associated with oceanic submesoscales requires simultaneous sampling at multiple locations. Here, the authors show that a swarm of 16 Mini-Autonomous Underwater Explorers (M-AUEs), whose 3D trajectories are measured near-continuously, can resolve features of the flow at these scales.